Combined effects of physical inactivity and acute hyperglycemia on arterial distensibility. (August 2017) - Montero, David; Dandanell, Sune; Oberholzer, Laura; Keiser, Stefanie; Breenfeldt-Andersen, Andreas; Haider, Thomas; Merlini, Mario; Meinild-Lundby, Anne-Kristine; Lundby, Carsten
Arterial distensibility, an independent predictor of cardiovascular events, is transiently increased with acute hyperglycemia (AHG) in healthy individuals. Whether this response interacts with physical inactivity remains unknown. We examined the effects of short-term bed rest (BR) on the response of carotid artery distensibility (CD) to AHG, and the influence of underlying changes in insulin resistance and blood volume. CD was assessed with ultrasonography before as well as 30 and 120 minutes following ingestion of 75 g of glucose prior to and after 3 days of BR in 15 healthy male volunteers. Plasma insulin/glucose concentrations and blood volumes were concomitantly determined. On day 4 of BR, blood volume was re-established to pre-BR levels by albumin infusion and CD and insulin/glucose concentrations were determined as in the previous experimental days. Basal CD was not affected by BR. AHG increased CD before and after BR but reached a higher peak increment after BR (12% vs 60% at 30 min OGTT, p =0.028). BR also increased the plasma insulin concentration during AHG ( p =0.007). In regression analyses, plasma insulin and glucose concentrations were positively correlated to CD, particularly after BR ( r =0.31, p <0.05). Restoration of the BR-induced loss (5%) in blood volume did not affect the response of CD to AHG. In conclusion, short-term physical inactivity strongly accentuates the initial increase in CD in response to AHG in healthy individuals. This effect is associated with concomitant increases in circulating insulin concentration attributable to early insulin resistance.